2010
DOI: 10.1021/ie100328v
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Diluents on The Synergistic Solvent Extraction and Separation of Trivalent Lanthanoids With 4-Benzoyl-3-Phenyl-5-Isoxazolone and tert-Butylcalix[4]Arene Tetrakis(N,N-Dimethyl Acetamide) and Structural Study of Gd(III) Solid Complex By IR and NMR

Abstract: The solvent extraction of 14 lanthanoid(III) ions from a chloride medium with acidic chelating extractant 4-benzoyl-3-phenyl-5-isoxazolone (HPBI) and tert-butylcalix[4]arene tetrakis(N,N-dimethylacetamide) (S) as a synergistic agent in C6H6 has been studied. In all cases, Ln(III) ions were extracted as Ln(PBI)3·S species. Positive values of the synergistic coefficients show that all lanthanoids were extracted synergistically upon the addition of compound S to the chelating extractant. The values of the equilib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
34
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 37 publications
3
34
0
Order By: Relevance
“…As part of our systematic work on the synergistic solvent extraction of lanthanoids, [1][2][3][4][5][6][7][8] we performed comparative studies aiming at (i) improving the extraction ability of b-diketone compounds by increasing their acidity, (ii) studying the dependence of the extraction properties on the number of the ligating groups on a calixarene scaffold and nally, (iii) understanding the role of the solvent for extraction, separation and synergism by comparing a traditional molecular solvent, chloroform, and one ionic liquid, namely 1-methyl-3-butylimidazolium bis(triuoromethanesulfonyl)imide, there-aer denoted as [C 1 C 4 im][Tf 2 N]. It is our opinion that the wellassessed strategy based on the individual independent improvements of the extractants used in a synergistic system, which has proven to be quite efficient in molecular solvents, [1][2][3][4][5][6][7][8] may nd some limitations in ionic liquids (ILs). Ionic liquids are studied for an increasing number of applications in various aspects of chemistry and of course liquid-liquid extraction of rare earths and other metals.…”
Section: Introductionmentioning
confidence: 99%
“…As part of our systematic work on the synergistic solvent extraction of lanthanoids, [1][2][3][4][5][6][7][8] we performed comparative studies aiming at (i) improving the extraction ability of b-diketone compounds by increasing their acidity, (ii) studying the dependence of the extraction properties on the number of the ligating groups on a calixarene scaffold and nally, (iii) understanding the role of the solvent for extraction, separation and synergism by comparing a traditional molecular solvent, chloroform, and one ionic liquid, namely 1-methyl-3-butylimidazolium bis(triuoromethanesulfonyl)imide, there-aer denoted as [C 1 C 4 im][Tf 2 N]. It is our opinion that the wellassessed strategy based on the individual independent improvements of the extractants used in a synergistic system, which has proven to be quite efficient in molecular solvents, [1][2][3][4][5][6][7][8] may nd some limitations in ionic liquids (ILs). Ionic liquids are studied for an increasing number of applications in various aspects of chemistry and of course liquid-liquid extraction of rare earths and other metals.…”
Section: Introductionmentioning
confidence: 99%
“…32 It could be supposed that the complexes containing two PDN1A15C5 molecules are sandwich type complexes having one PDN1A15C5 or BA15C5 moiety on either side of the metal chelate. A similar suggestion has been made earlier by Mathur and Khopkar 33 for the complexes obtained in the synergistic extraction of some actinoids and Eu(III) with acylpyrazolone and benzo-15-crown-5.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…Atanassova et al have already demonstrated that the extraction of Ln ions using the strongly coordinating compound HPBI in a set of molecular diluents proceeds through a proton-exchange reaction, forming neutral tris complexes. [23][24][25][26][27] The extraction mechanism and the extraction constant of the neutral tris complexes (Kex,3) were represented by the following equations:…”
Section: Mechanism Of Lanthanoids Extraction Using 4-benzoyl-3-phenylmentioning
confidence: 99%
“…(11) from slope analysis (data not shown in the figures). [23][24][25][26][27] In addition, the values of log Kex,3 for La 3+ , Eu 3+ , and Lu 3+ in the chloroform system were determined to be -1.34 ± 0.10, 0.85 ± 0.11, and 0.73 ± 0.10 by a linear leastsquares fitting of the plots, respectively. Electroneutrality is an essential principle, as only neutral complexes may enter the hydrophobic molecular layer.…”
Section: Mechanism Of Lanthanoids Extraction Using 4-benzoyl-3-phenylmentioning
confidence: 99%
See 1 more Smart Citation